Early Diagnostic Analysis of Chemistry Students’ Learning Profiles : Motivation, Study Habits, and Affective Factors - Sumiati Side; Ayu Ashari; Munawwarah Munawwarah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study reports an early diagnostic analysis of chemistry students’ learning profiles at the beginning of a course (n = 53). Using a mixed-methods descriptive survey, motivation and learning goals, study habits, affective factors, learning conditions, and brief reflections were collected and analyzed descriptively and thematically. Students showed high motivation and mastery-oriented goals (M = 4.40, SD = 0.35), but study habits were only moderate (M = 3.80, SD = 0.53), with regular studying showing the lowest tendency (M = 3.34). Affective results indicated moderate chemistry confidence (M = 3.83) but lower mathematics confidence (M = 3.32), alongside substantial test anxiety (M = 3.72; 58.49% agree). Contextually, most students reported ≤4 hours of weekly independent study time and varying learning environments 54.72% relied on smartphones with intermittently unstable internet. Qualitative themes emphasized conceptual difficulty, pacing, and quantitative demands, supporting the need for scaffolded instruction and flexible learning supports.